The Influence of the Perception of Health Benefits and Environmental Friendliness on Oat Drink Purchase Decisions - Altafni Mahdia; Harianto Harianto; Etriya Etriya (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Increasing public awareness of environmental and health issues has driven a shift in consumption patterns toward plant-based products, such as oat beverages, which are considered more environmentally friendly and healthier than cow's milk. In Indonesia, the consumption of oat beverages has increased; however, challenges remain, including limited consumer understanding of product benefits and intense market competition.Purpose: This study aims to identify the decision-making process involved in purchasing oat beverages and analyze the influence of packaging design, sensory attributes, labeling, perceived healthiness, and environmental friendliness on consumer purchasing decisions.Design/Methodology/Approach:  This study employed multistage random sampling and collected data through questionnaires to respondents who had previously purchased oat drinks and met the specified criteria. Data were collected offline through questionnaires administered to 230 respondents from three faculties at IPB University over a one-month period, from February to March 2025. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM).Results: Based on PLS-SEM analysis, all indicators meet the validity and reliability criteria. Labeling, perceived healthiness, and environmental friendliness are perceived to influence purchase decisions for oat drinks significantly. Packaging design, sensory attributes, control variables, namely age and expenditure do not affect the purchase decision. Conclusion: Clear product information and health and sustainability-related claims are key drivers of oat beverage purchasing decisions and can strengthen marketing strategies in a competitive market.Originality/value (State of the art): This study offers empirical evidence on consumer purchasing behavior for oat beverage purchasing decisions in Indonesia, highlighting labeling, health perception, and environmental friendliness as strategic considerations for marketing plant-based products. Keywords:   health perception, labeling, oat drink, packaging design, purchase decision